2015
DOI: 10.1111/bcpt.12394
|View full text |Cite
|
Sign up to set email alerts
|

Post‐Injection Delirium/Sedation Syndrome after Olanzapine Long‐Acting Intramuscular Injection – Who is at Risk?

Abstract: The post-injection olanzapine delirium/sedation syndrome (PDSS) was observed in a 60-year-old Caucasian, schizophrenic, non-smoker and underweight [body mass index (BMI), 18.2 kg/m 2 ] women after the fourth intramuscular injection of 405 mg olanzapine pamoate. Clinical symptoms of PDSS were similar to those of acute oral olanzapine intoxication. The patient received supportive treatment and recovered fully. High olanzapine concentrations in serum, with maximum level of 698 ng/mL, were confirmed by liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…route of administration. In particular, post-injection delirium/sedation syndrome, characterized by sedation (including coma) and/or delirium has been reported in approximately <0.1% of injections [133][134] Patients with cardiac impairment should be carefully monitored for the increasing risk of orthostatic hypotension. Although olanzapine is not recommended in children and adolescents, preliminary clinical data suggest its relative safety and efficacy for the treatment of behavioral disturbances.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…route of administration. In particular, post-injection delirium/sedation syndrome, characterized by sedation (including coma) and/or delirium has been reported in approximately <0.1% of injections [133][134] Patients with cardiac impairment should be carefully monitored for the increasing risk of orthostatic hypotension. Although olanzapine is not recommended in children and adolescents, preliminary clinical data suggest its relative safety and efficacy for the treatment of behavioral disturbances.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…A very high serum olanzapine concentrations, sometimes exceeding 600 ng/mL, was detected in some cases. 11 Regarding management, in some cases, anti-hypertensives and benzodiazepines were used but till now no definite plan of management was mentioned in any of the previous studies. 10…”
Section: Discussionmentioning
confidence: 99%
“…4 In the literature, cases of PDSS have been mostly reported to be associated with long-acting olanzapine injections. 5,6 Kokalj et al 7 reported a female patient with schizophrenia who developed symptoms ranging from confusion to delirium and anticholinergic symptoms after a long-acting olanzapine injection and high-dose oral paliperidone. In the safety investigations of a clinical study examining the relationship between long-acting risperidone and paliperidone palmitate with PDSS, no cases of PDSS associated with paliperidone palmitate and long-acting risperidone were detected.…”
mentioning
confidence: 99%
“…Postinjection delirium/sedation syndrome most commonly occurs within 5 hours after injection 4 . In the literature, cases of PDSS have been mostly reported to be associated with long-acting olanzapine injections 5,6 . Kokalj et al 7 reported a female patient with schizophrenia who developed symptoms ranging from confusion to delirium and anticholinergic symptoms after a long-acting olanzapine injection and high-dose oral paliperidone.…”
mentioning
confidence: 99%